The life cycle of a dog - Sexton, Colleen A., 1967- (Minneapolis, MN : Bellwether Media, 2010)
"Developed by literacy experts for students in kindergarten through grade three, this book follows dogs as they transform from puppies to adults. Through leveled text and related images, young readers will watch these creatures grow through every stage of life"--Provided by publisher.
Includes bibliographical references (p. 23) and index.
Keywords: Dogs -- Life cycles -- Juvenile literature